2009
DOI: 10.1007/s11251-009-9095-8
|View full text |Cite
|
Sign up to set email alerts
|

What makes a matrix so effective? An empirical test of the relative benefits of signaling, extraction, and localization

Abstract: What type of display helps students learn the most and why? This study investigated how displays differing in terms of signaling, extraction, and localization impact learning. In Experiment 1, 72 students were assigned randomly to one cell of a 4 9 2 design. Students studied a standard text, a text with key ideas extracted, an outline that localized ideas topically, and a matrix that localized ideas topically and categorically. One version of the displays signaled the displays' organization and one version did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…In a comparison of different types of representations for collaborative learning, Suthers and Hundhausen (2003) found that students working with matrix diagrams searched for relations between cells more than students working with graph or text. Kauffman and Kiewra (2009) found that localization in matrices bolstered both fact (separate cells) and relationship (combinations of cells) learning. Fig.…”
Section: Matrix Diagramsmentioning
confidence: 98%
See 2 more Smart Citations
“…In a comparison of different types of representations for collaborative learning, Suthers and Hundhausen (2003) found that students working with matrix diagrams searched for relations between cells more than students working with graph or text. Kauffman and Kiewra (2009) found that localization in matrices bolstered both fact (separate cells) and relationship (combinations of cells) learning. Fig.…”
Section: Matrix Diagramsmentioning
confidence: 98%
“…It allows topics to be easily compared along one or more categories (Kauffman and Kiewra 2009;Kiewra et al 1999). Matrices organize by localization, which refers to how close together similar information is placed on a printed page (Larkin and Simon 1987).…”
Section: Matrix Diagramsmentioning
confidence: 99%
See 1 more Smart Citation
“…These question types, contextualization, sourcing, and corroboration, correspond to Wineburg's (1991) historical thinking heuristics. These participants then received a matrix (Kauffman & Kiewra, 2010;Schraw, 1998) to guide notetaking while reading. Control condition participants also received the matrix to guide notetaking during reading but did not receive any instructions about question types or historical thinking.…”
Section: Effects Of Questioning On Multiple-document Readingmentioning
confidence: 99%
“…These experiments provided a valuable basis, as they indicated that specifically structured examples can sensitize learners to structural relationships Mayer 1996, 2002;Scheiter and Gerjets 2005). We presented these examples in the form of a matrix on a single page (for the benefits of well-structured matrices, see Kauffman and Kiewra 2009). To emphasize certain key concepts, we also adapted a paradigm used by McDaniel and Einstein (1989) where letter-completion tasks were used to facilitate the processing of individual idea units to complement relational processing.…”
Section: Materials and Instrumentsmentioning
confidence: 99%